“Orthodoxy” in the triad of S. S. Uvarov - Fyodor Gayda (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article is devoted to the fi rst element of the Uvarov triad Orthodoxy. Autocracy. Nationality. The previous historiographic tradition tends to view it as a formality, completely subordinated to the political demands of the autocracy. This article examines the understanding by the Minister of Public Education S. S. Uvarov (1833–1849) of Orthodoxy in the context of his views on the world’s history and Russian history, as well as the views of the Uvarov circle. The greatest infl uence on Uvarov’s ideas was exerted by N. M. Karamzin; one can also talk about the infl uence of A. S. Shishkov and M. P. Pogodin. The article concludes that Orthodoxy was conceived by Uvarov as one of the Russian “national principles” that had been established throughout the entire previous history. The Orthodox Church in Russia was strong because it was the Church of the Russian people, the Orthodox faith became part of the national identity. However, the people themselves were brought up in the spirit of Orthodoxy, which became the guarantee of its correct development. As Uvarov believed, the Orthodox faith was distinguished by the certainty of doctrine and retained its intact appearance. Thanks to this, Orthodoxy had the ability to further spread in the crisis of the Christian world. In Orthodoxy, spiritual freedom was preserved, which Christianity possessed due to its divine nature. Uvarov believed that the rejection of Christian truths inevitably led to a world catastrophe.